Determinants of vitamin D status in Kenyan calves - Callaby, R.; Hurst, E.; Handel, Ian G.; Toye, Philip G.; Bronsvoort, B.M. de C.; Mellanby, R.J. (Springer, 2020)
Vitamin D plays a critical role in calcium homeostasis and in the maintenance and development of skeletal health. Vitamin D status has increasingly been linked to non-skeletal health outcomes such as all-cause mortality, infectious diseases and reproductive outcomes in both humans and veterinary species. We have previously demonstrated a relationship between vitamin D status, assessed by the measurement of serum concentrations of the major vitamin D metabolite 25 hydroxyvitamin D (25(OH)D), and a wide range of non-skeletal health outcomes in companion and wild animals. The aims of this study were to define the host and environmental factors associated with vitamin D status in a cohort of 527 calves from Western Kenya which were part of the Infectious Disease of East African Livestock (IDEAL) cohort. A secondary aim was to explore the relationship between serum 25(OH)D concentrations measured in 7-day old calves and subsequent health outcomes over the following 12 months. A genome wide association study demonstrated that both dietary and endogenously produced vitamin D metabolites were under polygenic control in African calves. In addition, we found that neonatal vitamin D status was not predictive of the subsequent development of an infectious disease event or mortality over the 12 month follow up period.